1972
DOI: 10.1002/chin.197242366
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: UMWANDLUNGEN DER DIMETHYLSILYLAETHER VON O‐ UND P‐BROMPHENOLEN

Abstract: Der Trimethylsilyläther des o‐Bromphenols (I) setzt sich mit Dimethylchlorsilan (II) in Gegenwart von Magnesium zur Verbindung (III) um (Ausb. 86%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this manner, the following compounds containing heterocyclic rings of 9-10 atoms were synthesized: (Z)-2,2-dimethyl-7-[(4-methylphenyl)sulfonyl]-2,3,6,7-tetrahydrobenzo[h][1,7,2]oxazasilonine, (Z)-2,2-dimethyl-3,6-dihydro-2H-benzo[h][1,7,2]dioxasilonine, (Z)-8-isopropoxy-9-methoxy-3,3-dimethyl-1,3,4,7-tetrahydrobenzo[g]-[1,2]oxasilonine and (Z)-2,2,7,7-tetramethyl-2,3,6,7-tetrahydrobenzo[i] [1,8,2,7]dioxadisilecine. …”
mentioning
confidence: 99%
“…In this manner, the following compounds containing heterocyclic rings of 9-10 atoms were synthesized: (Z)-2,2-dimethyl-7-[(4-methylphenyl)sulfonyl]-2,3,6,7-tetrahydrobenzo[h][1,7,2]oxazasilonine, (Z)-2,2-dimethyl-3,6-dihydro-2H-benzo[h][1,7,2]dioxasilonine, (Z)-8-isopropoxy-9-methoxy-3,3-dimethyl-1,3,4,7-tetrahydrobenzo[g]-[1,2]oxasilonine and (Z)-2,2,7,7-tetramethyl-2,3,6,7-tetrahydrobenzo[i] [1,8,2,7]dioxadisilecine. …”
mentioning
confidence: 99%
“…The primary synthetic route to benzosilaoxetes was based upon ring formation by a metal catalyzed dehydrocondensation of a silyl hydride and an alcohol. The formation of Si-0 bonds using this methodology has ample precedent (114)(115)(116). In fact, Tumey has shown that silaoxetanes may be formed by similar dehydrocondensation reactions (12).…”
Section: Scheme 72mentioning
confidence: 99%
“…The precursors to the benzosilaoxetes were readily prepared according to the procedure of Mironov e;^ aj. (Scheme 79) (116,117). This two step synthesis generally afforded the desired ^-silylphenol in 50-60% overall yield.…”
Section: Scheme 72mentioning
confidence: 99%